2019
DOI: 10.1371/journal.pone.0222814
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of EGFR exon 19 deletion mutation using molecular dynamics simulation

Abstract: Epidermal growth factor receptor (EGFR) is a tyrosine kinase receptor important in diverse biological processes including cell proliferation and survival. Upregulation of EGFR activity due to over-expression or mutation is widely implicated in cancer. Activating somatic mutations of the EGFR kinase are postulated to affect the conformation and/or stability of the protein, shifting the EGFR inactive-active state equilibrium towards the activated state. Here, we examined a common EGFR deletion mutation, Δ746ELRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
0
16
1
1
Order By: Relevance
“…Periodic boundary conditions were implemented, and the particle-mesh Ewald algorithm was applied 79 for electrostatic interactions with a distance cutoff of 9 Å. For full details of the simulation protocol see Tamirat et al, 2019 80 . Conformations were saved every 10 ps and the resulting MD trajectories were analysed further by calculating the root-mean-square deviations (RMSD; over backbone atoms) and root-mean-square fluctuations (RMSF; over Cα atoms), as well as monitoring hydrogen bond interactions using CPPTRAJ 81 and VMD 82 .…”
Section: Methodsmentioning
confidence: 99%
“…Periodic boundary conditions were implemented, and the particle-mesh Ewald algorithm was applied 79 for electrostatic interactions with a distance cutoff of 9 Å. For full details of the simulation protocol see Tamirat et al, 2019 80 . Conformations were saved every 10 ps and the resulting MD trajectories were analysed further by calculating the root-mean-square deviations (RMSD; over backbone atoms) and root-mean-square fluctuations (RMSF; over Cα atoms), as well as monitoring hydrogen bond interactions using CPPTRAJ 81 and VMD 82 .…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the β3-αC loop attains different conformations, accounting for the higher RMSF of this region in D770insNPG EGFR in contrast to V769insASV EGFR. Indeed, the β3-αC loop is the location for multiple activating deletion mutations, where the shortening of this loop is postulated to impart structural stability to the nearby αC helix [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The deletions occur at the β3-αC loop and are suggested to affect the structural stability of the adjacent αC helix by limiting its range of motions [ 26 ]. Our previous study has indeed demonstrated that the most common EGFR exon 19 deletion, Δ746ELREA750, appears to stabilize the activated kinase domain state and drives a conformational shift from the inactive state towards the active EGFR state by affecting the structural and positional stability of the αC helix [ 27 ]. NSCLC patients with the L858R and exon19 deletion mutations respond to first- and second-generation tyrosine kinase inhibitors (TKIs), such as gefitinib, erlotinib, and afatinib; however, resistance is inevitably conferred mainly due to acquisition of a second mutation, the T790M “gate-keeper” mutation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This results from a decrease in the β3-αC loop flexibility, which stabilizes the αC-helix in the active αC-in conformation. Furthermore, the ∆ 746 ELREA 750 deletion causes an inwards conformational shift of the αC-helix, which disrupts the hydrophobic cluster in between the αC-helix, thereby promoting the activation of the TK domain [86].…”
Section: L858rmentioning
confidence: 99%
“…Similarly, to L858R point-mutants, Del19 EGFR mutants display a decreased affinity for ATP binding (K M ) and a lower K i for first-generation TKIs such as erlotinib [66,86]. However, exon 19 deletions and consequent residue insertions display large heterogeneity and thus exhibit differential drug sensitivity [85,91].…”
Section: L858rmentioning
confidence: 99%